The in-situ evaluation of surface-breaking cracks in asphalt using a wave decomposition method. Issue 4 (4th July 2021) - Iodice, M; Muggleton, J M; Rustighi, E
ABSTRACT: Damage in a pavement structure is usually initiated in the asphalt layers, making the Rayleigh wave ideally suited to the detection of shallow surface defects. However, the practical application of crack detection methods in asphalt is hampered by the dispersive behaviour of the road pavement. A new digital signal processing technique for the measurement of the amplitude and phase of the direct and reflected Rayleigh waves, scattered from the boundaries of a vertical crack in asphalt, is presented in this paper for the first time. The method uses multiple receivers and hence it finds an approximate solution with a least square optimisation. The resonant peak frequencies of the reflection coefficient and the cut-off frequencies of the transmission coefficient are used for assessing the depth of the crack. The method proved to be successful for the in-situ assessment of the depth of cracks both numerically and experimentally, since it can cope with the dispersive and heterogeneous nature of asphalt. This work supports a paradigm-shifting approach to the in-situ crack evaluation of roads, for which the road is holistically treated as a dispersive medium.